Analysis of Solid Medical Waste Management in Health Center - Elfandra Fadhli Rabbi; Eri Barlian; Nurhasan Syah; Indang Dewata (Postgraduate, University of Mataram, 2026)
Waste is the residue that arises from various human activities. Kersik Tuo Community Health Center is one of the largest producers of solid medical waste out of the twenty-one Community Health Centers in Kerinci Regency in 2024, amounting to 272 kg. The purpose of this study was to determine input components such as planning, labor and facilities and infrastructure, to see process components such as sorting, transportation, temporary storage and destruction, and to obtain output components related to solid medical waste management at Kersik Tuo Community Health Center, Kerinci Regency. This research method was carried out with a qualitative approach that aims to examine more deeply regarding solid medical waste management. The data collection technique used primary data with the determination of nine informants and secondary data. The technical data analysis in this study used the SWOT analysis method. The results of the study indicate that the input components have not been fully implemented properly, such as planning, workforce and facilities and infrastructure, then the process components have not been implemented properly, especially sorting, transportation, and temporary storage, and the output components related to the management of solid medical waste have not fully complied with PermenLHK P.56 of 2015.